Le chronotope de la peur dans les romans fantastiques d’Anne Duguël - Loska, Agnieszka (Romanica Silesiana)
Playing with reader’s fear is one of the objectives of fantastic literature. The present study, analysing two traditional fantastic motifs: of a ghost and of a dream, indicates the importance of time and space in Anne Duguël’s novels Gargouille and Le corridor. Particular attention was drawn to two space structures inextricably linked with time: the haunted house in Gargouille and the dream world in Le corridor. The aim of this analysis is to show how the author uses chronotope in order to arouse the reader’s fear. Key words: fear, neofantastic, ghost, dream, Anne Duguël